Determining official languages in the federal states in Nepal - Regmi, Dan Raj (Nepalese Linguistics, 2018)
While population is the major criterion for determining official languages, other criteria such as language vitality, identity, linguistic right, linguistic geography should be rationally evaluated along with population in terms of numeric rating scales. Exclusively based on merit list, official language should be recommended in the federal states in Nepal.